Puberty timing and adiposity change across childhood and adolescence: disentangling cause and consequence. Issue 12 (26th November 2020) - O'Keeffe, Linda M; Frysz, Monika; Bell, Joshua A; Howe, Laura D; Fraser, Abigail
Abstract: STUDY QUESTION: Is earlier puberty more likely a result of adiposity gain in childhood than a cause of adiposity gain in adulthood? SUMMARY ANSWER: Pre-pubertal fat mass is associated with earlier puberty timing but puberty timing is not associated with post-pubertal fat mass change. WHAT IS KNOWN ALREADY: Age at puberty onset has decreased substantially in the last several decades. Whether reducing childhood adiposity prevents earlier puberty and if early puberty prevention itself also has additional independent benefits for prevention of adult adiposity is not well understood. STUDY DESIGN, SIZE, DURATION: Prospective birth cohort study of 4176 participants born in 1991/1992 with 18 232 repeated measures of fat mass from age 9 to 18 years. PARTICIPANTS/MATERIALS, SETTING, METHODS: We used repeated measures of height from 5 to 20 years to identify puberty timing (age at peak height velocity, aPHV) and repeated measures of directly measured fat mass from age 9 to 18 years, from a contemporary UK birth cohort study to model fat mass trajectories by chronological age and by time before and after puberty onset. We then examined associations of these trajectories with puberty timing separately in females and males. MAIN RESULTS AND THE ROLE OF CHANCE: In models by chronological age, a 1-year later aPHV was associated with 20.5% (95% confidence interval (CI): 18.6–22.4%) and 23.4% (95% (CI): 21.3–25.5%) lower fat mass in females and males, respectively, at 9 years. These differences were smaller at age 18 years: 7.8% (95% (CI): 5.9–9.6%) and 12.4% (95% (CI): 9.6–15.2%) lower fat mass in females and males per year later aPHV. Trajectories of fat mass by time before and after puberty provided strong evidence for an association of pre-pubertal fat mass with puberty timing, and little evidence of an association of puberty timing with post-pubertal fat mass change. The role of chance is likely to be small in this study given the large sample sizes available. LIMITATIONS, REASONS FOR CAUTION: Participants included in our analyses were more socially advantaged than those excluded. The findings of this work may not apply to non-White populations and further work examining associations of puberty timing and fat mass in other ethnicities is required. WIDER IMPLICATIONS OF THE FINDINGS: Previous research has relied on self-reported measures of puberty timing such as age of voice breaking in males, has lacked data on pre-and post-pubertal adiposity together and relied predominantly on indirect measures of adiposity such as BMI. This has led to conflicting results on the nature and direction of the association between puberty timing and adiposity in females and males. Our work provides important clarity on this, suggesting that prevention of adiposity in childhood is key for prevention of early puberty, adult adiposity and associated cardiovascular risk. In contrast, our findings suggest that prevention of early puberty without prevention of childhood adiposity would have little impact on prevention of adult adiposity. STUDY FUNDING/COMPETING INTEREST(S): The UK Medical Research Council and Wellcome (Grant ref: 102215/2/13/2) and the University of Bristol provide core support for Avon Longitudinal Study of Parents and Children (ALSPAC). L.M.O.K. is supported by a UK Medical Research Council Population Health Scientist fellowship (MR/M014509/1) and a Health Research Board (HRB) of Ireland Emerging Investigator Award (EIA-FA-2019-007 SCaRLeT). J.A.B. is supported by the Elizabeth Blackwell Institute for Health Research, University of Bristol and the Wellcome Trust Institutional Strategic Support Fund (204813/Z/16/Z). L.D.H. and A.F. are supported by Career Development Awards from the UK Medical Research Council (grants MR/M020894/1 and MR/M009351/1, respectively). All authors work in a unit that receives funds from the UK Medical Research Council (grant MC_UU_00011/3, MC_UU_00011/6). No competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.